2020
DOI: 10.1007/s11356-020-08714-3
|View full text |Cite
|
Sign up to set email alerts
|

Does globalization in Turkey induce increased energy consumption: insights into its environmental pros and cons

Abstract: Globalization is the paradigm shift to a more integrated world economy broadly shaping economies and societies around the globe. The wave of globalization is much more eminent on its impact on increased energy demand, knowledge and technology transfer, trade, and financial capital flows. The present study focuses on Turkey, a fast-emerging economy that is no exception to the wave of globalization. This current study explores the dynamics between ecological footprints, energy consumption, and real income level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 89 publications
(68 reference statements)
2
37
0
Order By: Relevance
“…In understanding these impacts, the environmental Kuznets curve (EKC) is widely adapted to investigate the interactive influences and casual relationship of components that promotes emission (Shahbaz et al 2013;Tariq et al 2017). Hence, EKC model explains the complementary relatedness of socio-eco-environmental variables as they influence carbon emissions, as empirical investigations on the theme has attracted contrary views due to differences in The role of tourism on emissions is an addition to a number of other interrelated macroeconomic variables (Adedoyin et al 2020a, b;Adedoyin et al 2020a, c, b;Adedoyin and Zakari 2020;Etokakpan et al 2020;Kirikkaleli et al 2020;Udi et al 2020). For instance, tourism is recognized as a driver of economic expansion (Ouyang and Lin 2017;Wang et al 2016;Hossain 2011;Yu et al 2012) which in turn is responsible for the increasing CO 2 emission globally (Dogan and Seker 2016;Dogan and Turkekul 2016;;Wang et al 2016;Dogan et al 2020;Ertugrul et al 2016;Inglesi-Lotz and Dogan 2018;Moutinho et al 2018;Wang et al 2017;Zameer and Wang 2018;Wen and Shao 2019;Yasmeen et al 2020) and this threatens the environmental sustenance since this emission leads to extensive global warming.…”
Section: Introductionmentioning
confidence: 99%
“…In understanding these impacts, the environmental Kuznets curve (EKC) is widely adapted to investigate the interactive influences and casual relationship of components that promotes emission (Shahbaz et al 2013;Tariq et al 2017). Hence, EKC model explains the complementary relatedness of socio-eco-environmental variables as they influence carbon emissions, as empirical investigations on the theme has attracted contrary views due to differences in The role of tourism on emissions is an addition to a number of other interrelated macroeconomic variables (Adedoyin et al 2020a, b;Adedoyin et al 2020a, c, b;Adedoyin and Zakari 2020;Etokakpan et al 2020;Kirikkaleli et al 2020;Udi et al 2020). For instance, tourism is recognized as a driver of economic expansion (Ouyang and Lin 2017;Wang et al 2016;Hossain 2011;Yu et al 2012) which in turn is responsible for the increasing CO 2 emission globally (Dogan and Seker 2016;Dogan and Turkekul 2016;;Wang et al 2016;Dogan et al 2020;Ertugrul et al 2016;Inglesi-Lotz and Dogan 2018;Moutinho et al 2018;Wang et al 2017;Zameer and Wang 2018;Wen and Shao 2019;Yasmeen et al 2020) and this threatens the environmental sustenance since this emission leads to extensive global warming.…”
Section: Introductionmentioning
confidence: 99%
“…While the study of Bekun et al (2019) finds that natural resources aggravates the level of emissions in the environment, that of Balsalobre-Lorente et al (2018) argues that natural resource rents lead to an improvement in the environment. While several studies have shown emissions arising from several factors (F. Adedoyin et al, 2020b , 2020a ; Adedoyin et al, 2020c , 2020d , 2020e ; Adedoyin and Zakari, 2020 ; Etokakpan et al, 2020 ; Kirikkaleli et al, 2020 ; Udi et al, 2020 ), there are two ways to control carbon dioxide and other greenhouse gas emissions from energy usage in agriculture ( Li et al, 2016 ), one is to increase the efficiency of the energy, the other is to increase renewable energy usage.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…The increased exploitation of energy resources by man is now resulting in the increasing absorptions of the CO 2 by the world climate (Adedoyin et al 2020c, d, e;Etokakpan et al 2020;Nathaniel et al 2020d). Many countries in the world are experiencing significant changes in climatic conditions due to overdependence on a fossil energy source which allows for the increasing greenhouse emission (Işik et al 2017b;Pandey et al 2020).…”
Section: Introductionmentioning
confidence: 99%